Information System Requirements Analysis for MSME Digitalization Using the SDLC Waterfall Approach - Alvan Dhan; Angelina Apriyani Pandiangan; Nadita; Ratih Echa Kurnia; Rafi Akmal Rizqullah (RAM PUBLISHER, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the economy; however, they still face various challenges in adopting digital technology. This study aims to examine the requirements of an information system to support the digitalization of MSMEs using the Software Development Life Cycle (SDLC) Waterfall model. The research focuses on the analysis and design stages, which include identifying user requirements, analyzing business processes, and designing the system using Unified Modeling Language (UML). The results indicate that the proposed system should be capable of supporting integrated product management, transactions, ordering processes, and sales reporting, involving key actors such as buyers, sellers, and administrators. This study produces a system requirements model that can serve as a foundation for developing digital applications for MSMEs, thereby improving operational efficiency and enhancing business competitiveness.